The impact of retailer’s economic and social satisfaction on its commitment, and the moderating effect of manufacturer brands’ strength - Goaill, Majid Mapkhot; Perumal, Selvan; Mohd Noor, Nor Azila (Canadian Center of Science and Education, 2014)
Available literatures have confirmed that there are unstable and complex relationship between manufacturers and large retailers especially in the growing strength of retail organizations in the global context. This study thus examines the impacts of retailer’s satisfaction dimensions on its commitment, and the moderating effect of the manufacturer brands’ strength on the relationships between retailer’s satisfaction dimensions, and its commitment.This quantitative study presents the empirical findings from a survey of 140 large retailers using partial least squares (PLS). The results indicate that retailer’s economic and social satisfaction have strong positive influence on retailer’s commitment, and surprisingly, the retailer’s social satisfaction is more influential on its commitment than retailer’s economic satisfaction. The study also found that the strength of manufacturer’s brands enhances the relationship between retailer’s economic satisfaction and its commitment, but not the relationship between retailer’s social satisfaction and its commitment. Theoretical and managerial implications are extracted from these findings.